The insect-specific Palm Creek virus modulates West Nile virus infection in and transmission by Australian mosquitoes. Issue 1 (December 2016) - Hall-Mendelin, Sonja; McLean, Breeanna; Bielefeldt-Ohmann, Helle; Hobson-Peters, Jody; Hall, Roy; van den Hurk, Andrew
Abstract Background Insect-specific viruses do not replicate in vertebrate cells, but persist in mosquito populations and are highly prevalent in nature. These viruses may naturally regulate the transmission of pathogenic vertebrate-infecting arboviruses in co-infected mosquitoes. Following the isolation of the first Australian insect-specific flavivirus (ISF), Palm Creek virus (PCV), we investigated routes of infection and transmission of this virus in key Australian arbovirus vectors and its impact on replication and transmission of West Nile virus (WNV). Methods Culex annulirostris, Aedes aegypti andAedes vigilax were exposed to PCV, and infection, replication and transmission rates in individual mosquitoes determined. To test whether the virus could be transmitted vertically, progeny reared from eggs oviposited by PCV-inoculatedCx. annulirostris were analysed for the presence of PCV. To assess whether prior infection of mosquitoes with PCV could also suppress the transmission of pathogenic flaviviruses, PCV positive or negativeCx. annulirostris were subsequently exposed to WNV. Results No PCV-infectedCx. annulirostris were detected 16 days after feeding on an infectious blood meal. However, when intrathoracically inoculated with PCV, Cx. annulirostris infection rates were 100 %. Similar rates of infection were observed inAe. aegypti (100 %) andAe. vigilax (95 %). Notably, PCV was not detected in any saliva expectorates collected from any of these species. PCV was not detected in 1038 progeny reared from 59 PCV-infectedCx. annulirostris . After feeding on a blood meal containing 107 infectious units of WNV, significantly fewer PCV-infectedCx. annulirostris were infected or transmitted WNV compared to PCV negative mosquitoes. Immunohistochemistry revealed that PCV localized in the midgut epithelial cells, which are the first site of infection with WNV. Conclusions Our results indicate that PCV cannot infectCx. annulirostris via the oral route, nor be transmitted in saliva or vertically to progeny. We also provide further evidence that prior infection with insect-specific viruses can regulate the infection and transmission of pathogenic arboviruses.